Identification of types of landings after blocking in volleyball associated with risk of ACL injury - Zahradnik, D.; Jandacka, D.; Farana, R.; Uchytil, J.; Hamill, J. (European Journal of Sport Science, 2017)
Landing with a low knee flexion angle after volleyball block jumps may be associated with an increased risk of anterior cruciate ligament (ACL) injury. The aim of the present study was to identify the types of volleyball landings after blocks where the knee flexion angle is found to be under a critical knee flexion angle value of 30° at the instant of the first peak of the ground reaction force (GRF). Synchronized kinematic and kinetic data were collected for each trial. T-tests were used to determine if each knee flexion angle at the instant of the peak GRF was significantly different from the critical value of 30°. A repeated measures ANOVA was used to compare knee flexion angle, time to first peak and the magnitude of the first peak of the resultant GRF and knee stiffness. Significantly lower knee flexion angles were found in the "go" landing (p = .01, ES = 0.6) and the "reverse" landing (p = .02, ES = 0.6) only. The results for knee flexion angle and GRF parameters indicated a significant difference between a "reverse" and "go" and other types of landings, except the "side stick" landing for GRF. The "reverse" and "go" landings may present a risk for ACL injury due to the single-leg landing of these activities that have an associated mediolateral movement.